Kidney Dosimetry in 177Lu and 90Y Peptide Receptor Radionuclide Therapy: Influence of Image Timing, Time-Activity Integration Method, and Risk Factors. (20th June 2013) - Guerriero, F.; Ferrari, M. E.; Botta, F.; Fioroni, F.; Grassi, E.; Versari, A.; Sarnelli, A.; Pacilio, M.; Amato, E.; Strigari, L.; Bodei, L.; Paganelli, G.; et al.
Abstract : Kidney dosimetry in 177 Lu and 90 Y PRRT requires 3 to 6 whole-body/SPECT scans to extrapolate the peptide kinetics, and it is considered time and resource consuming. We investigated the most adequate timing for imaging and time-activity interpolating curve, as well as the performance of a simplified dosimetry, by means of just 1-2 scans. Finally the influence of risk factors and of the peptide (DOTATOC versus DOTATATE) is considered. 28 patients treated at first cycle with 177 Lu DOTATATE and 30 with 177 Lu DOTATOC underwent SPECT scans at 2 and 6 hours, 1, 2, and 3 days after the radiopharmaceutical injection. Dose was calculated with our simplified method, as well as the ones most used in the clinic, that is, trapezoids, monoexponential, and biexponential functions. The same was done skipping the 6 h and the 3 d points. We found that data should be collected until 100 h for 177 Lu therapy and 70 h for 90 Y therapy, otherwise the dose calculation is strongly influenced by the curve interpolating the data and should be carefully chosen. Risk factors (hypertension, diabetes) cause a rather statistically significant 20% increase in dose (t -test, P < 0.10 ), with DOTATATE affecting an increase of 25% compared to DOTATOC (t -test, P < 0.05 ).